Genetic characterization of F0 outbred and F1 inbred Swiss albino mice using microsatellite markers and their performance evaluation - TARANG, MITEK; KUMAR, PUSHPENDRA; KUMAR, AMIT; SAINI, B L; KAUSHAL, SHOBHANA; SACHAN, SHWETA; CHAUHAN, ANUJ; PRAKASH, JAI; BHUSHAN, BHARAT (The Indian Journal of Animal Sciences, 2021)
Swiss albino mice have been widely utilized in various biological researches worldwide. Phenotypic and fitness related traits of F0 and F1 inbred mice were estimated on 918 and 707 individual offsprings, respectively. The influence of fixed effects (litter size and sex) on birth weight (BW), weaning weight (WW) and adult body weight (ABW) in both the generations were found to be statistically significant. Genetic characterization of F0 outbred and the F1 inbred strain of Swiss albino mice were evaluated by using 10 microsatellites markers. The results indicated that total number of alleles per locus ranged from 3 (D2Mit61, D3Mit55, D8Mit14, D9Mit27, D10Mit180, D11Mit167) to 4 (D1Mit15, D2Mit51, D5Mit18, D7Mit323) in F0 and F1 inbred population, with a mean value of 3.4 indicating polymorphism in all 10 loci. The mean of effective number of alleles was 2.935 and 2.733 in F0 and F1 population, respectively. Estimates of the FIS ranged from 0.139 (D10Mit180) to 0.999 (D9Mit27); and from 0.109 (D3Mit55) to 0.679 (D2Mit51) in F0 and F1 inbred population, respectively. The estimated mean markerbased FIS was 0.294 and 0.372 in F0 and F1 populations, respectively. The mean values of observed heterozygosity (Ho) and expected heterozygosity (He) were 0.460 and 0.654, respectively for F0 and 0.390 and 0.627, respectively for F1 inbred mice population. Slight reduction in heterozygosity and 7.8% increase in inbreeding coefficient were observed in F1 inbred in comparison to F0 population. The results suggested that genome wide microsatellite genotyping might be more useful for accurate measuring and reliable estimation of population genetic parameters and inbreeding coefficient.